Knight's 24-hour trainer Microsoft SQL server 2008 integration services - Knight, Brian 1976- (Wiley Pub., 2009)
A unique book-and-video package for learning Microsoft SQL Server Integration Services. If you need a practical, hands-on introduction to Microsoft SQL Server 2008 Integration Services (SSIS), this book and video package from foremost SSIS authority Brian Knight gets you thoroughly up to speed. Each lesson in the book includes three major components: a thorough description of how each SSIS feature or process works; a tutorial that walks you through the process or technique; and a video lesson that demonstrates it. If you take full advantage of this comprehensive package, you will gain enough e.